Transfer of gene encoding for DNA unwinding helicase (pdh45) into tobacco plants (Nicotiana tabacum L. cv Xanthi) by using Agrobacterium and Analysis of the Transformed plants - Hoi, Pham Xuan; Quy, Tran Duy; Nghia, Phan Tuan; Tuteja, Narendra (Academia Journal of Biology, 2015)
PDH45, a DNA unwinding enzyme, has been determined to be an important multifunctional protein involved in the regulation of the protein synthesis, maintaining the basic activities of the cell and in the up regulation of the topoisomerase I activity (Pham et al., 2000). To understand the functional significance of PDH45 in plants, we introduced the PDH45 cDNA into the plant transformation pBI121 vector in both sense and antisense orientations under the control of the same strong constitutive CaMV 35S promoter. The Agrobacterium tumefaciens strain LBA 4404 was transformed with the sense and antisense constructs and recombinant colonies were selected on kanamycin plates. The presence of recombinant plasmids in the kanamycin resistant colonies was confirmed by PCR and restriction digestion. Transgenic plants were obtained by co-cultivation of recombinannt Agrobacterium tumefaciens and a leaf disc of Nicotiana tabacum cv xanthi. A total of 100 kanamycin resistant plants for each sense and antisense orientations were selected for further analysis. 50 of each sense and antisense plants were analyzed for PCR and GUS assay. All PCR reactions led to positive products and twelve with sense and ten with antisense were GUS positive. The morphology change in antisense transgenic plants as compared with wild type plant has been observed at T1 generation. The altered morphology was observed from the callus generation media where antisense plants formed less and weak callus but faster growing. In rooting media, antisense transgenic plants gave rise to increase in greenness and the leaves were thicker, more hairy, and slightly lanceolate of compact appearance, internode distance decreased and unsmooth lamina. The change was observed in a large population of antisense transgenic plants and has continued during all plant development. In addition, some antisense transgenic plants had flowered earlier and resulted in shortening of the time for the plant growth compared to the sense transgenic plants.